CD4+ T Cells Alter the Stromal Microenvironment and Repress Medullary Erythropoiesis in Murine Visceral Leishmaniasis - Preham, Olivier; Pinho, Flaviane A.; Pinto, Ana Isabel; Rani, Gulab Fatima; Brown, Najmeeyah; Hitchcock, Ian S.; Goto, Hiro; Kaye, Paul M. (Frontiers in Immunology, 2018)
Human visceral leishmaniasis, a parasitic disease of major public health importance in developing countries, is characterized by variable degrees of severity of anemia, but the mechanisms underlying this change in peripheral blood have not been thoroughly explored. Here, we used an experimental model of visceral leishmaniasis in C57BL/6 mice to explore the basis of anemia following infection with Leishmania donovani. 28 days post infection, mice showed bone marrow dyserythropoiesis by myelogram, with a reduction of TER119+ CD71-/+ erythroblasts. Reduction of medullary erythropoiesis coincided with loss of CD169high bone marrow stromal macrophages and a reduction of CXCL12-expressing stromal cells. Although the spleen is a site of extramedullary erythropoiesis and erythrophagocytosis, splenectomy did not impact the extent of anemia or affect the repression of medullary hematopoiesis that was observed in infected mice. In contrast, these changes in bone marrow erythropoiesis were not evident in B6.Rag2-/- mice, but could be fully reconstituted by adoptive transfer of IFN-producing but not IFN-deficient CD4+ T cells, mimicking the expansion of IFN-producing CD4+ T cells that occurs during infection in wild type mice. Collectively, these data indicate that anemia during experimental murine visceral leishmaniasis can be driven by defects associated with the bone marrow erythropoietic niche, and that this represents a further example of CD4+ T cell-mediated immunopathology affecting hematopoietic competence.